Does the Utilization of Allograft Tissue in Medial Patellofemoral Ligament Reconstruction in Pediatric and Adolescent Patients Restore Patellar Stability?. Issue 6 (June 2017) - Hohn, Eric; Pandya, Nirav K.
Abstract: Background: Medial patellofemoral ligament (MPFL) reconstruction is one of several surgical procedures used to treat patellofemoral instability. Use of allograft tissue can preserve autogenous tissue and may be preferable in patients with connective tissue disorders or ligamentous laxity. Although there are successful reports in adults, it is unclear if the use of allograft tissue in MPFL reconstruction can restore patellofemoral stability in children and adolescents. Questions/purposes: (1) Does allograft tissue in MPFL reconstruction in pediatric and adolescent patients restore patellar stability? (2) What complications were associated with allograft MPFL reconstructions in children and adolescents? Methods: Between June 2012 and August 2015, one surgeon (NKP) performed 26 MPFL reconstructions in 23 patients with gracilis allograft for traumatic patellar instability. Of those, 25 (96%) were available for followup more than 1 year later (mean, 24 months; range, 12‐44 months). During this time, the surgeon suggested reconstruction to patients who had recurrent dislocation or subluxation after 6 weeks of bracing, physical therapy, and activity modification if they were noted to have a torn or attenuated MPFL on MRI. During that period, this was the only surgical technique the surgeon used to treat traumatic patellar instability. Patients undergoing concurrent bony procedures were ineligible for inclusion. The mean age of the patients in the series was 16.0 (± 2) years. Age, sex, skeletal maturity, presence of trochlear dysplasia, and additional arthroscopic procedures at the time of reconstruction were collected. Postoperative notes and imaging were reviewed for presence of complications defined as recurrent dislocation, recurrent subluxations, fractures, infection, or arthrofibrosis. These complications were identified by chart review by the senior surgeon (NKP) and study personnel (EH) not involved in clinical care of the patients or by patient‐reported complications. Recurrent subluxation or dislocation was patient‐reported at the time of the clinic visit or followup phone/email contact. Fractures were defined as any cortical disruption in the femur or patella that required treatment (change in postoperative protocol), infection requiring treatment (antibiotics and/or return to the operating room), or arthrofibrosis (stiffness that necessitated a change in the postoperative protocol or manipulation under anesthesia). Results: Ninety‐two percent (23 of 25) of patients reported no further instability episodes after MPFL reconstruction. Sixteen percent (four of 25) of patients had complications: two repeat episodes of patellar instability, one patella fracture, and one symptomatic hardware requiring interference screw removal. No patients developed arthrofibrosis or infection. Conclusions: In this small case series, we found that MPFL reconstruction using allograft tissue in children and adolescents resulted in a low risk of recurrent instability, perhaps comparable to what has been published by others who have used autograft tissue. Longer followup is needed, because in some orthopaedic applications, allograft ligaments have been observed to attenuate over time. Future studies might compare these techniques using patient‐reported outcomes scores as well as use a control group of patients with autograft tissue. Level of Evidence: Level IV, therapeutic study.